High performance teams: do perceptions and reality match - Dominguez, Caroline (2016)
Effective team management is one of the key factors that allow companies to tackle the challenges of today’s demanding business environment. Although high-performing teams have been studied for some time, very little has been written on them from the construction industry’s perspective. Based on the conclusions of previous work and on a project involving 44 professionals of seven teams, this exploratory case study intends to evaluate if there is a gap between what team members and leaders perceive as being (a) the most important features for managing teams into high performance and (b) the features that are present in their teams. The present study shows that, although teams under investigation had some high-performing features at the leadership dimension, there is room for improvement, in particular when it comes to empowering team members, involving them in planning the work, and creating proper reward systems.